2019
DOI: 10.1097/corr.0000000000000995
|View full text |Cite
|
Sign up to set email alerts
|

Women Are at Higher Risk for Concussions Due to Ball or Equipment Contact in Soccer and Lacrosse

Abstract: Background There is ample evidence to suggest sex- and gender-based differences in the incidence of sports-related concussions. The mechanisms of concussion may vary between male and female athletes and contribute to this observed difference. Understanding the underlying etiology by pooling data from primary studies across different settings and sport types will inform interventions that can reduce concussion rates. Questions/purposes Specifically, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Specifically, although the most common reported cause of SRC in male athletes was contact with another player, accounting for almost half of SRCs recorded in males, in female athletes the most common mechanism was contact with an object (41.9%). These findings echo those reported in a meta-analysis 27 of high school and college sports that revealed female soccer athletes were more likely to sustain an SRC from contact with a ball, including during heading, or equipment and less likely to sustain a concussion from player contact than male athletes. In general, soccer ball heading has been considered an infrequent direct cause of SRC, 28 although it is widely recognized that collision with opponents during heading can result in concussion.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, although the most common reported cause of SRC in male athletes was contact with another player, accounting for almost half of SRCs recorded in males, in female athletes the most common mechanism was contact with an object (41.9%). These findings echo those reported in a meta-analysis 27 of high school and college sports that revealed female soccer athletes were more likely to sustain an SRC from contact with a ball, including during heading, or equipment and less likely to sustain a concussion from player contact than male athletes. In general, soccer ball heading has been considered an infrequent direct cause of SRC, 28 although it is widely recognized that collision with opponents during heading can result in concussion.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, for sex-comparable high school and collegiate sports, studies have suggested SRC incidence to be higher among girls’ and women’s sports compared with boys’ and men’s sports. 19,26,29 Previous studies also have illustrated player and apparatus contact to be the primary mechanisms attributed to SRCs in this population among men’s and women’s sports, respectively. 9,37…”
mentioning
confidence: 71%
“…Previous studies have shown that women experience more concussions in sexcomparable sports 17 and that in ball-based sports like lacrosse and soccer, women are at higher risk for concussions due to contact with the ball or equipment. 19 Furthermore, in soccer, women are more likely to sustain concussions when heading the ball or while goalkeeping. 18 This study builds on these findings by demonstrating that this sex-based discrepancy in primary sports concussion incidence is observed with concussion recurrence as well.…”
Section: Discussionmentioning
confidence: 99%
“…18 In particular, the mechanism of injury (MOI) differs between male and female athletes, with player contact being the predominant MOI in men and equipment contact being the predominant MOI in women. 19 A study by van Ierssel et al found that children and adolescents who have sustained previous concussions have nearly four times greater risk of a recurrent concussion compared to those with no previous concussion incidence. 20 Our metaanalysis aimed to compare recurrent concussion incidence between male and female athletes across various sports.…”
Section: Introductionmentioning
confidence: 99%